SARSNTdb database: Factors affecting SARS-CoV-2 sequence conservation - Orgera, John; Kelley, James J.; Bar, Omri; Vaidhyanathan, Sathyanarayanan; Grigoriev, Andrey (Frontiers in Virology, 2022)
SARSNTdb offers a curated, nucleotide-centric database for users of varying SARS-CoV-2 knowledge. Its user-friendly interface enables querying coding regions and coordinate intervals to find out the various functional and selective constraints that act upon the corresponding nucleotides and amino acids. Users can easily obtain information about viral genes and proteins, functional domains, repeats, secondary structure formation, intragenomic interactions, and mutation prevalence. Currently, many databases are focused on the phylogeny and amino acid substitutions, mainly in the spike protein. We took a novel, more nucleotide-focused approach as RNA does more than just code for proteins and many insights can be gleaned from its study. For example, RNA-targeted drug therapies for SARS-CoV-2 are currently being developed and it is essential to understand the features only visible at that level. This database enables the user to identify regions that are more prone to forming secondary structures that drugs can target. SARSNTdb also provides illustrative mutation data from a subset of ~25,000 patient samples with a reliable read coverage across the whole genome (from different locations and time points in the pandemic. Finally, the database allows for comparing SARS-CoV-2 and SARS-CoV domains and sequences. SARSNTdb can serve the research community by being a curated repository for information that gives a jump start to analyse a mutation’s effect far beyond just determining synonymous/non-synonymous substitutions in protein sequences.